2020
DOI: 10.1177/1090198120907887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health Literacy and Depression Literacy Among Korean Americans

Abstract: Low health literacy is closely related to a higher rate of hospitalization and of emergency services usage, leading to billions of dollars in avoidable health care costs and contributing to individuals’ poor physical and mental health. While Korean Americans (KAs) have a high prevalence of general health and mental health problems, relatively little is known about their health and mental health literacy, specifically their depression literacy. This study aims to evaluate KAs’ health literacy and depression lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…As demonstrated by several previous studies, 16,17,23 educational level is an imperative factor influencing health literacy among Korean immigrants residing in the U.S. for all age groups, potentially due to its possible relationship with English proficiency, which research have found direct influence on health literacy. 9,20,24 However, the present study found that, for Korean citizens, educational level was only found to significantly influence health literacy among those aged 65 and older. One possibility for this difference in findings could be how aging and generational differences uniquely influence the understanding of and accessibility to health services in Korean citizens aged 65 and older.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…As demonstrated by several previous studies, 16,17,23 educational level is an imperative factor influencing health literacy among Korean immigrants residing in the U.S. for all age groups, potentially due to its possible relationship with English proficiency, which research have found direct influence on health literacy. 9,20,24 However, the present study found that, for Korean citizens, educational level was only found to significantly influence health literacy among those aged 65 and older. One possibility for this difference in findings could be how aging and generational differences uniquely influence the understanding of and accessibility to health services in Korean citizens aged 65 and older.…”
Section: Discussioncontrasting
confidence: 72%
“…16,17,23 Some have considered education as an enabling factor because of its relationship with English proficiency and social economic status, both of which facilitate the acquisition of health literacy. 9,20,24 However, it is more commonly considered as a predisposing factor because it does not fluctuate and pertains to the fixed social status that a person has already obtained. The enabling factors examined in the present study included whether the individual had private health insurance coverage, a designated place for medical care, a doctor in charge, and the frequency of doctor visits.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study revealed that HL level was found to rise with increasing education levels for both the tools and income, only for the HLQ tool [29]. Bernstein et al, proposed that education had a major impact on health literacy as senior citizens with a lower level of education are more likely to have a limited HL [21,30].…”
Section: Discussionmentioning
confidence: 99%